Diphtheria outbreak in a district in Meghalaya, India: an overview - Bhattacharyya, Himashree; Sarkar, Amrita; Medhi, Gajendra K.; Pala, Star (International Journal Of Community Medicine And Public Health, 2016)
Diphtheria is an infectious disease which has continued to cause illness and death in children even after the advent of vaccine and diphtheria anti-toxin. Since, immunization is an important tool against this disease, countries with poor immunization coverage still continue to experience several outbreaks of diphtheria, both reported and unreported. India is one of the worst affected counties of diphtheria and here mortality remains to be high as well due to unavailability of diphtheria anti-toxin. The present article aims to highlight one such outbreak in the remote part of North-eastern region of the country wherein diphtheria anti-toxin is not available in the entire region making the chances of fatality higher. A total of 7 cases of diphtherias were found in the present outbreak. Case fatality rate was 28.6%.6 out of the 7 cases were unvaccinated. Low immunization coverage along with poor living conditions as well as ignorance of community was found to be the major risk factors leading to this outbreak.